Can Interfaith Research Resolve the Global Conflicts Based on Faith? - Mahmoud, Mahgoub El-Tigani (European Scientific Journal, ESJ, 2017)
Interfaith issues are quite central in the contemporary life as they had often been in ancient times. In the light of political striving, violence, and deep global concerns for the world order and peace, a great many people have been increasingly inspired to know about religions of the world, their similarities and differences, the roles they may play in conflict and conflict resolution, and the ways most desirable to get their members to know one another in justice and peace, regardless of the size of followers a religion enjoys or the tenets of faith they enjoin. Judaism, Christianity, and Islam maintain ancestral ties with a unique origin, namely the Abrahamic scriptural and spiritual heritages the Talmud, the Bible, and the Qur’an literally contained. These holy books contain a great wealth of knowledge about God and His messengers who enlightened mankind with the wisdom of religion to pursue the good life with perseverance and moral values. The discourse of interfaith ideals and practices has been in great demand globally, despite a few endeavors to enhance authentic knowledge about religion, in general, and the monotheistic religions, in particular. The need of the world is largely felt to appreciate the true meanings of religious life for individuals and social groups in order to advance the cause of peaceful co-existence between peoples of the world, especially in areas suffering deep ideological hostilities or prolonged violence through the negative influences of religious intolerance.